A Sustainable Approach To Oral Care: Formulation Of Herbal Toothpaste And Medicated Chewing Gum Using Eggshell Calcium And Clove Oil - Bhosle, Snnehaa; kajbaje, Rucha; Todkari, Priyanka; Deshmukh, Meera; Tilak, Praniti (Journal of Neonatal Surgery, 2025)
Herbal oral care products incorporating eggshell-derived calcium and clove oil were developed as a dual strategy for sustainable, therapeutic dental care. This work combines two formulations – a calcium-rich herbal toothpaste and a medicated chewing gum – both utilizing eggshell powder (as a natural calcium carbonate source) and clove oil (as an analgesic and antimicrobial agent). Eggshell waste, composed of ~95% calcium carbonate, was processed into a fine powder to serve as an abrasive and remineralizing component. Clove oil, rich in eugenol (~72–90% of oil content), provides potent antibacterial and pain-relieving properties for oral health. The toothpaste was formulated with eggshell powder alongside standard excipients, and the chewing gum was prepared using a gum base matrix incorporating eggshell-derived calcium and clove oil as the active ingredient. Both products were evaluated on physicochemical parameters, organoleptic properties, and performance benchmarks. Results indicate that the optimal toothpaste batch achieved neutral pH, acceptable foaming (50 mL), smooth texture, and no sharp particles, while the leading chewing gum batch showed ideal chewing consistency (hardness ~4.5 kg/cm²), low moisture (<5%), minimal friability (<0.6%), and sustained clove flavor release. Table 1 compares key evaluation parameters of the formulations. These findings demonstrate the feasibility of repurposing eggshell waste into value-added oral care products and confirm that the combination of eggshell calcium and clove oil can yield effective, natural alternatives for dental hygiene. The discussion addresses formulation challenges, highlights the role of eggshell calcium in remineralization and clove oil in oral therapeutics, and outlines the broader implications for sustainable product development.